The Effectiveness of Traffic and Road Transport Law Policies in Reducing the Violation Rate of Highway Users in the Territory of Indonesia - Aji Primanto; Linda Puspitasari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Traffic problems that are increasingly complex today cannot be separated from population growth and the development of community dynamics that are always changing from time to time. Traffic and road transportation problems in Indonesia are not only about increasing the number of people every year but also with various levels of education ranging from the uneducated to the intellectuals (heterogeneous), as well as the different socio-economic levels of the students. road users, causing a different level of absorption of traffic norms. To overcome this, the government began to issue and implement Law No. 22 of 2009 concerning Road Traffic and Transportation. From the results of the research that has been carried out, it can be seen that the Effectiveness of the Traffic and Road Transport Law Policy in Reducing the Violation Rate of Highway Users has not been able to be implemented optimally in the Indonesian Territory. It is proven by the fact that there are still many violations committed by two-wheeled riders, which amounted to 660,072 violations and four-wheelers as many as 199,916 violations. While the types of violations that are mostly committed by two-wheeled riders are that they do not use helmets when driving on the highway with a total of 186,570 violations, and the violations committed by four-wheeled users are that they often violate road markings with a total of 72,909 violations.